The viability of introducing no fault liability insurance in land registration: a pilot study / Habibah Kiprawi … [et al.] - Kiprawi, Habibah; Abu Bakar, Noraziah; Abu Hassan, Norila; Datuk Salleh, Rafidah (Faculty of Law, 2012)
The aim of this research is to examine the viability of introducing no fault liability insurance to registered proprietors and innocent victims who through no fault of theirs lose their property either through forgery or fraudulent dealings. The scheme will provide compensation to innocent victims who has no other means of recovering their property which they have lost through illegal means such as fraud or forgery. Currently there is no recourse available to innocent victims or registered proprietors in such dealings other than to make a police report or to sue the parties involved. However if the party who committed fraud or forgery could not be traced the innocent victims are left with no option but to make a police report and wait for the outcome of the investigation by the police. If those con artist cannot be traced then there is no remedy at all available to the innocent victims. Hence there is a need to introduce no fault liability insurance in land transaction to compensate victims who otherwise would not have any form of protection or compensation at all. This study will look into issues such as the amount of premium, public reception especially registered proprietors and property investors as well as the government’s willingness to implement the proposed insurance model or compensation fund. This pilot study will adopt a qualitative approach including semi-structured interviews with the respective respondents i.e. the Attorney General Chambers, Bar Council, practitioners, insurance companies and registered proprietors.